Selection of internal reference gene for normalization of reverse transcription-quantitative polymerase chain reaction analysis in Mycoplasma hyopneumoniae - Li, Shiyang; Zhou, Yanqing; Yuan, Ting; Feng, Zhixin; Zhang, Zhenzhen; Wu, Yuzi; Xie, Qingyun; Wang, Jia; Li, Quan; Deng, Zhibang; Yu, Yanfei; Yuan, Xiaomin (Frontiers in Veterinary Science, 2022)
Mycoplasma hyopneumoniae is the etiological agent of swine enzootic pneumonia (EP). EP results in considerable economic losses in pig farming globally. Reverse transcription quantitative polymerase chain reaction (RT-qPCR) is a major tool for gene expression studies. No internal reference genes for normalization of RT-qPCR data of M. hyopneumoniae have been reported. The aim of this study was to screen the most stable genes for RT-qPCR analysis in M. hyopneumoniae under different conditions. A total of 13 candidate internal reference genes (rpoC, Lipo, sgaB, oppB, hypo621, oppF, gyrB, uvrA, P146, prfA, proS, gatB, and hypo499) of M. hyopneumoniae filtered according to the reported quantitative proteomic analysis, and the 16S rRNA internal reference gene frequently used in other bacteria were selected for RT-qPCR analysis. The mRNAs from different virulence strains (168, 168 L, J, NJ, and LH) at five different growth phases were extracted. The corresponding cycle threshold (Ct) values of the 25 reverse transcribed cDNAs using the 14 candidate genes were determined. Different internal reference genes or combinations were screened for expression stability analysis using various statistical tools and algorithms, including geNorm, BestKeeper, and NormFinder software, to ensure the reliability of the analysis. The results of geNorm analysis showed that the expression of gyrB and gatB were the most stable, while the stability of gatB and prfA were the highest in NormFinder analysis and gatB and gyrB were the most stable genes in BsetKeeper analysis. Through further comprehensive evaluation of RefFinder software, it is concluded that the gatB gene was the most suitable internal reference gene for samples of the different virulence strains in different growth phases for M. hyopneumoniae, followed by prfA, hypo499 and gyrB.